Case report: Malignant proliferating trichilemmal tumor of the thumb - Wang, Guojie; Zhou, Xuan; Luo, Junqi; Hu, Qiyi; Zhang, Jie (Frontiers in Oncology, 2022)
Proliferating trichilemmal tumor is a very rare benign tumor that has the potential to transition into a malignant tumor. PTT most commonly affects the scalps of women above 60 years old and is frequently misdiagnosed due to its rarity. Herein, we present a case of a 68-year-old man with a malignant proliferating trichilemmal tumor on his right thumb. X-ray image showed a soft tissue mass on his thumb accompanied by bone destruction, while 18F-FDG PET revealed a hypermetabolic mass in the first index with axillary lymph node metastasis.